Sauvés de l’oubli - Marianne Berissi (Amnis)
The analysis of Peter Sis’picture book, The Wall. A Chilhood Behind the Iron Curtain, and Tomi Ungerer's autobiographical work, Tomi, a Childhood under the Nazis, focuses on the status of ego documents and archive in historical stories for youth. In these works, listening to a singular voice that traces the birth of an artistic vocation takes precedence over didactic preoccupation.